UJI KEAMANAN WPA2 DENGAN WI-FI DEAUTHER MENGGUNAKAN AEROWPA - Ruswanti, Diyah; Susilo, Dahlan (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
Almost every home has a Wi-Fi (Wireless Fidelity) internet connection, and it is normal practice to safeguard internet access to prevent unauthorized use and to make sure that internet usage does not exceed costs. Using WPA (Wi-Fi Protected Access) protection is one method of securing internet access over Wi-Fi. However, some people are still attempting to crack WPA2 in order to obtain unrestricted, free, and unauthorized access to the internet. The purpose of this study is to identify the ways in which AeroWPA can be utilized to mitigate the problem of obtaining WiFi access without a password. AeroWPA and Wi-Fi Deauther are used in the keamanan access control procedure, with the Router Nirkabel Totolink N300RT serving as the subject of the investigation in order to identify any kind of anomaly. The study's findings indicate that the process of changing a password in an AeroWPA script is hindered by password cracking, which causes a connected phone to freeze twice. Additionally, SSID security is compromised by using a password that is obtained from a logged-in user and the script itself employs Social Engineering.